Putting Daoist thought into practice : Happiness, longevity, and enlightenment. - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2024)
This book shows how Chinese wisdom originating many centuries ago is still highly relevant to our lives today as the Daoist classics provide insightful prescriptions on how to live a life full of happiness, contentment, and healthy longevity. They also provide guidance regarding personal ethics, sustainable economics, and achieving enlightenment.The book contains reflections on how to achieve happiness drawing from the Liezi, a Daoist classic, and it examines Daoist ideas about nourishing life to achieve longevity and the marked similarity between these principles and people living in “blue zones” today with the highest concentration of centenarians. It explores Daoist views on consciousness and enlightenment in the Laozi and Zhuangzi and their close resemblance to some of the most influential “new age” teachings on the subject. It highlights the ethical character of a Daoist sage by drawing on the Daoist classic of the Wenzi and enumerates lessons for transitioning toward a sustainable economy from the Daodejing.Covering multiple dimensions of classical Daoist thought and their contemporary applications to human development and well-being, this text will usefully inform scholars, students, and researchers of Asian studies, religion, and philosophy, and individuals seeking self-improvement and personal wellness.